Pengembangan Media Berbasis Wordwall untuk Meningkatkan Motivasi Belajar Bahasa Indonesia Siswa Kelas II MI - Marwah, Sopa; Siti Anisah, Ani; Handayani, Safitri; Najwa Nabila, Zain (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Indonesian language learning in lower grades of Madrasah Ibtidaiyah still faces the problem of low student learning motivation due to the limited use of interactive learning media that align with students’ developmental characteristics. This study aimed to develop Wordwall-based interactive learning media and to analyze its feasibility and effectiveness in enhancing the Indonesian language learning motivation of second-grade Madrasah Ibtidaiyah students. This study employed a Research and Development approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 24 second-grade students of MI Al-Junaediyah, Garut Regency. The research instruments included interview guidelines and observation sheets for needs analysis, expert validation sheets for material and media feasibility assessment, and a learning motivation questionnaire using a four-point Likert scale to measure media effectiveness. Data were analyzed using descriptive and inferential statistics with the Wilcoxon test. The results showed that the Wordwall-based interactive learning media were categorized as very valid, with a feasibility percentage of 88.13%, and that the learning motivation questionnaire demonstrated good reliability with a Cronbach’s alpha value of 0.74. The results of the Wilcoxon test show that the Asymp. Sig. (2-tailed) value is smaller than the significance level (a=0.05), demonstrating a significant improvement in students’ learning motivation after the implementation of the Wordwall-based learning media. Therefore, the Wordwall-based interactive learning media are feasible and effective in enhancing Indonesian language learning motivation among second-grade Madrasah Ibtidaiyah students.